Laboratory investigation on microcrack fracturing behaviour of granite under quasi-static combined compression and shear - He, Qingyuan; Liu, Zhibing; Li, Yingchun; Li, Danqi (Geomechanics and geophysics for geo-energy and geo-resources., 2021)
The mechanical characteristics of brittle materials submitted to combined compression and shear loading (CCSL) have received considerable attention recently. Both dynamic and quasi-static CCSL tests have been experimented to simulate the realistic working conditions encountered by different materials. Nevertheless, how the external shear loading affects the microcrack fracturing of rock still excludes explanation. In this paper, a self-developed loading device, instrumented with acoustic emission monitoring, is used to uncover the effect of sample inclination on the microcrack fracturing thresholds of granite samples sourced from two different places. Our laboratory results show that the microcrack damage thresholds (σ cd ) of the granite samples drop almost linearly with higher sample inclination whereas the microcrack initiation thresholds (σ ci ) only decline when the inclination angle is elevated to a certain magnitude. The changes of the σ ci /σ c ratios (the σ ci to peak strength ratios) and the σ cd /σ c ratios against the sample inclination are rock origin dependent. Multiple regression analysis is conducted to unveil the correlation among microcrack fracturing thresholds, peak strength and sample inclination. Both σ ci and σ cd are more sensitive to the combined influence of the peak strength and the inclination angle compared with the individual effect of these two factors. Finally, empirical formulae are proposed to provide reliable predictions of σ ci and σ cd at different sample inclination based on the peak strength acquired from the CCSL tests. Article Highlights Microcrack fracturing of granite specimen under quasi-static CCSL is studied with a self-developed loading device and acoustic emission monitoring. How the specimen inclination affects the microcrack fracturing thresholds of granite specimens and their ratios to the specimen peak strength are understood. Microcrack fracturing thresholds of granite specimens are found to be more sensitive to the combined effect of the specimen peak strength and the inclination angle compared with the individual effect of these two factors. Empirical formulae are proposed to give quick, reliable prediction of the microcrack fracturing thresholds of granite specimens at different specimen inclination.